2007
DOI: 10.1177/1049732307302668
|View full text |Cite
|
Sign up to set email alerts
|

The Preservation of Order: The Use of Common Approach Among Staff Toward Clients in Long-Term Psychiatric Care

Abstract: The authors performed this grounded theory study to gain a deeper understanding of the kinds of social processes that lead to a need among psychiatric nursing staff to reach a common approach on how to act toward individual clients in long-term psychiatric care. They present a theory about the development of such common approaches among staff. The main findings were that in psychiatric group dwellings, when the internal order is perceived as having been disturbed, the staff preserve or restore the internal ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…The structural analysis contributed a more explanatory view by highlighting that differences were manifested not only in different opinions but also in different ways of relating to the suffering person. Therefore, literature focusing on a common staff approach (Enarsson et al 2007(Enarsson et al , 2008, different forms of presence (Fredriksson 1999) and caring conversations as a means to alleviate suffering (Fredriksson & Eriksson 2001 provides the theoretical basis for critical reflection.…”
Section: Critical Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural analysis contributed a more explanatory view by highlighting that differences were manifested not only in different opinions but also in different ways of relating to the suffering person. Therefore, literature focusing on a common staff approach (Enarsson et al 2007(Enarsson et al , 2008, different forms of presence (Fredriksson 1999) and caring conversations as a means to alleviate suffering (Fredriksson & Eriksson 2001 provides the theoretical basis for critical reflection.…”
Section: Critical Reflectionmentioning
confidence: 99%
“…Furthermore, they can side with their peers, avoiding both being alienated from them and becoming overwhelmed by patients' suffering. As a consequence, patients are met with different strategies aiming at fostering an acceptable behaviour that fits the cultural demands of the unit (Enarsson et al 2007). By overlooking suffering rather than approaching and alleviating it, nurses can avoid becoming personally involved in and touched by patients' suffering.…”
Section: Critical Reflectionmentioning
confidence: 99%
“…However, reality is not always comparable with the ideal. Sometimes patients do not wish to receive the care offered by nurses; nurses can handle such situations in different ways, for example through using a common staff approach (Enarsson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously performed a grounded theory study, (Enarsson, Sandman & Hellzén, 2007) with the aim of gaining a deeper understanding of the kinds of social processes that lead psychiatric nursing staff to formulate a common approach on how to act towards individual patients in long-term psychiatric care. The study showed how an order-disturbing incident that could not be dealt with within existing routines, and for which no similar previous experiences were available to base solutions on, led the staff to restore order by assuming certain attitudes and/or acting in certain ways towards a patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation